Efficacy and safety of concurrent chemoradiotherapy with cisplatin and docetaxel in patients with locally advanced nasopharyngeal cancers - (:unkn) unknown (My University, 2013)
Aims and background. Chemoradiation using cisplatin-based regimens has become the standard care in the treatment of nasopharyngeal cancers. The impact of taxanes as radiosensitizing agents with concurrent chemoradiation regimens is unknown. We retrospectively evaluated the efficacy and tolerability of weekly cisplatin + docetaxel combination with chemoradiation in locally advanced nasopharyngeal cancers. Methods. Forty-two patients with locally advanced nasopharyngeal cancers (59.5% stage IV, 23.3% stage III, and 16.7% stage II) were assessed retrospectively. Total radiation dose to the planning target volume of gross disease (primary and/or node) was 70 Gy/35 fractions, 5 fractions per week. Minimum doses of 60 Gy and 50 Gy were administered to planning target volume of elective high-risk and low-risk disease, respectively. Chemotherapy consisted of weekly cisplatin (20 mg/m2) + docetaxel (20 mg/m2) concurrently with radiotherapy. Results. The median age of the patients was 46.5 years (range, 17-79). Objective response rate was 86%. The 4-year progression-free survival and overall survival were 65.4% and 91.3%, respectively. The most common grade 3 and 4 toxicities were mucositis (48%), nausea (22%), neutropenia (12%), dermatitis (5%), fatigue (5%) and weight loss (5%). Conclusions. Weekly cisplatin and docetaxel concurrent with radiotherapy for locally advanced nasopharyngeal cancers was found tolerable with a high efficacy.
Keywords: Chemoradiotherapy; Cisplatin; Docetaxel; Nasopharyngeal cancer